Electroacupuncture Improves Trinitrobenzene Sulfonic Acid-Induced Colitis, Evaluated by Transcriptomic Study. (5th June 2014) - Ho, Tin-Yun; Lo, Hsin-Yi; Chao, De-Cheng; Li, Chia-Cheng; Liu, Jau-Jin; Lin, Chingju; Hsiang, Chien-Yun
Abstract : Inflammatory bowel disease is a chronic colonic inflammation that displays symptoms like diarrhea and weight loss. Acupuncture has been widely accepted by Western countries for the treatment of pain. Here, we analyzed efficacy and mechanism of electroacupuncture (EA) on trinitrobenzene sulfonic acid- (TNBS-) induced colitis in mice. Mice were intrarectally administered with 250 mg/kg TNBS and electroacupunctured at Quze (PC3) and Neiguan (PC6) acupoints, which have been applied for gastrointestinal disorders. Gene expression profiles in colons and spleens were analyzed by microarray for the elucidation of mechanism of EA. Our data showed that EA at PC3 and PC6 improved macroscopic and microscopic features of colitis and the improvement displayed a frequency-dependent manner. Administration of TNBS upregulated the expression of most cytokine genes in colons, while EA downregulated the expression of TNBS-induced cytokine genes. Pathway analysis showed that EA significantly affected inflammatory pathways in colons and immunity-associated pathway in spleens. Immunohistochemical staining further showed that EA decreased the expression of interleukin-1 β and nuclear factor- κ B. In conclusion, this is the first study reporting the global gene expression profiles of EA on TNBS-induced colitis. Our findings suggested that inflammatory and immunity pathways were involved in the anti-inflammatory mechanism of EA on colitis induced by TNBS.